INTEGRASI GENDER DALAM PENGUATAN EKONOMI MASYARAKAT PESISIR - RITA NUR SUHAETI; EDI BASUNO (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
To implement gender mainstreaming activity in relation to regional development,mainly for coastal development, a study on gender mainstreaming had been carried intwo districts, namely Buton in Southeast Sulawesi and Cirebon in West Java out fromJune to December 2003. Data and information were collected using Focused GroupDiscussion approach as well as village level profiles and monograph. Gender analysisusing Harvard Framework was implemented, covering profiles of participation, access,control and influencing factors. The study results showed that in Buton, labor divisionbetween man and woman in sea weed farming was relatively balanced. Participation rateof the household members, both in domestic, public and social sector in both studiedlocations was relatively similar. The role of Women Empowerment Division of TheAgency for Society Empowerment (ASE) in Cirebon has not been optimal and stilllearning to find out suitable activities to meet its mandates. In Buton District, there was acoordination problem in implementing gender mainstreaming program, because therewere two institutions both claimed responsible in implementing gender mainstreamingprogram. One important thing that has never been conducted in the two districts was tocreate collaboration among institutions responsible for the gender mainstreamingimplementation. In the future, The District Level Marine and Fishery Service Officeshould work in collaboration with the ASE and they have to discuss how to incorporategender aspects in coastal development including in Economic Empowerment for CoastalCommunity.